Effects of speed, agility, and quickness training on athletic performance: a systematic review and meta-analysis - Sun, M.; Soh, K. G.; Cao, S.; Yaacob, A. B.; Ma, S.; Ding, C. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Previous studies have demonstrated the effects of SAQ training on sprint, change-of-direction, and jump performance in soccer players. However, further research is needed to assess its broader impact on different athletic populations and performance metrics. This study aims to expand the existing evidence by incorporating a wider range of outcomes and providing a more comprehensive analysis of SAQ training effects.